JAK2 V617F‐positive acute myeloid leukaemia (AML): a comparison between de novo AML and secondary AML transformed from an underlying myeloproliferative neoplasm. A study from the Bone Marrow Pathology Group. (16th May 2018) - Aynardi, Jason; Manur, Rashmi; Hess, Paul R.; Chekol, Seble; Morrissette, Jennifer J. D.; Babushok, Daria; Hexner, Elizabeth; Rogers, Heesun J.; Hsi, Eric D.; Margolskee, Elizabeth; Orazi, Attilio; Hasserjian, Robert; et al.
Summary: The JAK2 V617F mutation is characteristic of most Philadelphia chromosome‐negative myeloproliferative neoplasms (MPNs) and occurs rarely in de novo acute myeloid leukaemia (AML). We sought to characterize AMLs that harbour this mutation and distinguish those that arise de novo (AML‐DN) from those that reflect transformation of an underlying MPN (AML‐MPN). Forty‐five patients with JAK2 V617F‐mutated AML were identified; 15 were AML‐DN and 30 were AML‐MPN. AML‐MPN cases were more likely to have splenomegaly ( P  = 0·02), MPN‐like megakaryocytes and higher mean JAK2 V617F VAF at diagnosis ( P  = 0·04). Mutations involving TET2 were exclusively identified in AML‐DN patients. Mutations of genes affecting DNA methylation were more common in AML‐DN ( P  < 0·01). A complex karyotype was more frequent in AML‐MPN cases than in AML‐DN ( P  < 0·01), with AML‐DN more likely to display a normal karyotype ( P  = 0·02). Bone marrow histology after recovery from induction chemotherapy in AML‐DN cases revealed no morphological evidence of any previously occult MPNs, while this was evident in most of the AML‐MPN specimens ( P  < 0·01). These findings in this largest study of JAK2 V617F‐mutated AMLs indicate that AML‐DN is distinct from AML‐MPN.